Advanced relay technologies in next generation wireless communications - Krikidis, Ioannis; Zheng, Gan (IET telecommunications series ;, 2016)
Cooperative networks/relaying is a fundamental design approach that has been used to reduce path-loss and fading effects in conventional wireless communication systems. This book describes the use of this approach in new and emerging telecommunications technologies and new application areas. Topics covered include spatial modulation for cooperative networks; relaying for massive MIMO; relaying for outdoor to indoor in mmWave communications; precoding techniques for relaying with interference; relaying in full-duplex radio communication systems; relay selection in modern communication systems; relaying in green communications systems; energy-efficient relaying; cognitive radio with relaying; relaying in non-ideal conditions; relaying and physical layer secrecy; relaying technologies for smart grid; simultaneous wireless and power transfer for interference relay channel; relaying in visible light communication systems; and on-ground and on-board signal processing for multibeam. With contributions from an international panel of experts, this book is essential reading for researchers and advanced students in academia and industry working in telecommunications system design.